Lewis Pair Catalyzed Regioselective Polymerization of (E, E)‐Alkyl Sorbates for the Synthesis of (AB)n Sequenced Polymers. (5th October 2021) - Zhao, Wuchao; Li, Fukuan; Li, Chengkai; He, Jianghua; Zhang, Yuetao; Chen, Changle
Abstract: In this contribution, Lewis pairs (LPs) composed of N‐heterocyclic olefins (NHOs) with different steric hindrance and nucleophilicity as Lewis bases (LBs) and Al‐based compounds with comparable acidity but different steric hindrance as Lewis acids (LAs) were applied for 1, 4‐selective polymerization of (E, E)‐methyl sorbate (MS) and (E, E)‐ethyl sorbate (ES). The effects of steric hindrance, electron‐donating ability, and acidity of LPs on MS and ES polymerization were systematically investigated. High catalytic activity and high initiation efficiency can be achieved, leading to the formation of PMS with 100 % 1, 4‐selectivity, tunable molecular weight (Mw up to 333 kg mol −1 ), and narrow molecular weight distribution (MWD). Block copolymerization of ES and methyl methacrylate (MMA) was also realized. Meanwhile, this system can be applied to other homologous conjugated diene substrates. Furthermore, simple chemical reactions can efficiently convert PMS to different polymers with strict (AB) n sequence structures, such as poly(sorbic acid), poly(propylene‐alt‐methyl acrylate), poly(propylene‐alt‐acrylic acid), poly(propylene‐alt‐allyl alcohol), and poly(ethylene‐alt‐2‐butylene). Abstract : Lewis pairs were applied for living/controlled and 1, 4‐selective polymerization of sustainable ( E, E )‐alkyl sorbates. Poly(( E, E )‐alkyl sorbates) could be further converted into various polymers with strict (AB) n sequence structures, such as poly(sorbic acid), poly(propylene‐ alt ‐methyl acrylate), poly(propylene‐ alt ‐acrylic acid), poly(propylene‐ alt ‐allyl alcohol), and poly(ethylene‐ alt ‐2‐butylene).